Reviewing the current diagnostic and treatment approaches for myocarditis – analysis of literature - Zys, Damian; Wojszczyk, Maciej; Ryniecka, Julia; Czyż, Witold; Kacperczyk, Julia; Chuncia-Ileczko, Marta; Wójcikiewicz, Michalina; Arczewski, Filip; Dziedzic, Karol; Kulbacka, Julia (Quality in Sport, 2025)
Introduction: Myocarditis is an inflammatory disease of the heart muscle, presenting with symptoms ranging from mild discomfort to severe cardiac dysfunction. It poses diagnostic challenges due to overlap with conditions such as coronary artery disease and its nonspecific presentation. This review summarizes current diagnostic and therapeutic approaches, emphasizing advancements in imaging and personalized treatment strategies. Aim of the study: The aim of this study was to summarize the existing knowledge of currently relevant diagnostic and therapeutic approaches to myocarditis, highlighting both established methods and emerging advances. Materials and Methods: The literature available in the PubMed database was reviewed using the following keywords: "myocarditis," "myocarditis diagnosis," "myocarditis treatment," "diagnosis of myocarditis," "COVID-19 myocarditis," "viral myocarditis," and "autoimmune myocarditis." Conclusions: Myocarditis is a complex and multifactorial condition that requires improved diagnostic tools and individualized treatment strategies. As with other diseases, personalized approaches considering patient-specific factors are essential for better clinical outcomes. To achieve this, further research into innovative diagnostic methods and targeted therapies is necessary. Additionally, raising awareness of myocarditis is crucial for early diagnosis, timely treatment, and patient support.